Silica-based mesoporous ion-imprinted fluorescent sensors for the detection of Pb2+ in aqueous environments. (5th March 2023) - Xu, Qingming; Lv, Jie; Wu, Tongfei; Hu, Bo; Li, Yunhui; Zeng, Fanming; Zhu, Jianwei
Abstract: In this work, an environment-friendly core–shell material based on CDs@SiO2 as the core and mesoporous ion-imprinted layer as the shell was reported. As a highly sensitive and accurate fluorescent sensor for the detection of Pb 2+ in environmental water, the composition combined ion imprinting technology with quantum dots to selectively quench the fluorescence of CDs by metal coordination in the presence of Pb 2+, and the visual change of gradually weakening blue color could be observed by the naked eye for visual detection. The mesoporous structure significantly improved the detection recognition rate of CDs@SiO2 @MIIPs.The molecularly imprinted sensor presented a favorable linear relationship over a Pb 2+ concentration range from 10 nmol l −1 to 100 nmol l −1 and a detection limit of 2.16 nmol l −1 for Pb 2+ . The imprinting factor of the CDs@SiO2 @MIIPs was 5.13. The sensor has a fast detection rate, is highly selective in the identification of Pb 2+, and can be reused up to 10 times. The applicability of the method was evaluated by the determination of Pb 2+ in spiked environmental water samples with satisfactory results.